RESEARCH OF SOLID BIOFUEL PRODUCTION TECHNOLOGY - KUPCHUK, IHOR; BYSTRYTSKYI, OLEXANDER (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is devoted to the review and analysis of the solid biofuel production process using various types of raw materials. The article describes the process of crushing raw materials using different types of crushers and highlights the features of each of them. The effectiveness of various raw material grinding methods was also analyzed and their impact on the quality and properties of solid biofuel granules was determined. It was noted that the optimal particle length for granulation depends on the type of raw material and may be different for different types of biomass. In addition, the influence of various impurities on the quality and properties of solid biofuel pellets, such as dust, metal pieces, plastic impurities, etc., was investigated. It was found that the presence of impurities in raw materials can significantly worsen the quality and properties of solid biofuel granules, so it is necessary to carry out quality control at each stage of production. The process of biofuel production using thermochemical methods, such as pyrolysis and gasification, has also been investigated. Data on the effectiveness of using each of the methods and their impact on the quality and properties of biofuel are presented. The process of solid biofuel compression and granulation is considered, and data on the influence of various factors on the quality and properties of granules are given.